PERAN PENYULUH BAGI NELAYAN DI KELURAHAN PALABUHANRATU KABUPATEN SUKABUMI - Rinda Noviyanti (Berkala Perikanan Terubuk, 2017)
The research was conducted on August 2015 until November 2015. Extension activities conducted by the Department of Fisheries West Java province is one way to increase knowledge of fishermen. The purpose of this research is to see the role of extension for fishermen in Palabuhanratu Village, Sukabumi Regency, West Java Province. The method used by survey methods with 48 respondents. The analysis is done descriptively qualitative. Based on the research results can be showed that according to 77.1% of respondents there are extension officers from the Department of Fisheries who provide counseling. Respondents who actively follow the extension there are 35.4%. According to the majority of respondents (68.8%), counseling is conducted with a frequency that is not fixed or incidental. Only 16.7% of respondents stated extension materials according to their needs. Based on the results of this research, the role of extension workers is still not maximal, where the extension activities related to time and material activities are still not well programmed, and the material presented has not met the needs of the fishermen in order to increase their knowledge and skills